INTERSENTENTIAL CODESWITCHING AMONG INDONESIAN-ENGLISH BILINGUALS - Hamzah, Hamzah (English Department FBS UNP, 2010)
This study is aimed at investigating how the English-Indonesian bilingual speakers use language codes in their interaction through internet. The data for this study comprised a linguistic corpus made up from postings send to a newsgroup by its members. The findings showed that codeswitching accured in this forum was similar to that in the face to face interaction. The code choice may be either marked or unmarked. The unmarked switching occured during informal and relax interaction. While the marked switching occured when the speakers wanted to negotiate a new right and obligation, specifically when they wanted to show anger, attract attention, make correction or invite another speaker to join.